Analysis of Factors Affecting Non-Performing Loan at PT Xyz Financing Company Before and During Covid-19 (2018-2022) - Aditya Sajudi; Hermanto Siregar; Bayu Bandono (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
Non-Performing Loan is a situation where the ratio of the volume of non-performing loans (arrears >30 days) to total loans. This study aims to analyse the factors that influence the amount of credit (total loans) and the factors that influence Non-Performing Loan at PT XYZ in the range of 2018-2022. This study aims to analyse the factors that influence the amount of credit (total loans) at PT XYZ measured using multiple linear regression methods, while the factors that influence Non-Performing Loan at PT XYZ are measured using Binary Logistic Regression. The data in this study uses secondary data from PT XYZ in 2018-2022. The results of this study indicate that the factors that affect the amount of credit are Vehicle Price, Effective Rate, Installment Value per month, amount of downpayment (DP), total financing, tenor, age, education, gender, marital status, occupation and unit type, while the factors that affect the chances of customers becoming NPF are inflation, customer area and covid-19 pandemic and the Sumatra area is an area that needs special attention because it has a 121.4% higher chance of becoming an NPL.